2017
DOI: 10.1039/c7py00295e
|View full text |Cite
|
Sign up to set email alerts
|

Bis(2-oxo-7-azaindolin-3-ylidene)benzodifuran-dione-based donor–acceptor polymers for high-performance n-type field-effect transistors

Abstract: Two donor–acceptor (D–A) conjugated polymers were synthesized using a strongly electron-deficient unit as the acceptor, and dithiophene and (E)-2-(2-(thiophen-2-yl)vinyl)thiophene as the donor units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…By using the same azaBDO monomer and copolymerizing it with an alkylated bithiophene ( P42 ) and TVT comonomers, Zhang et al were able to continue with and further expanded this concept (note: P42 – P44 are not shown in Figure due to their close similarities to the other BDO polymers that we have shown in Figure ), reporting electron mobilities of up to 1.86 cm 2 V −1 s −1 * . A similar fluorination strategy to Lei et al was reported by Zheng et al Here they used a tetra‐fluorinated BDO monomer ( P43 ), suggesting that the fluorination might have a double function as a conformational lock.…”
Section: N‐type Organic Semiconductorssupporting
confidence: 62%
“…By using the same azaBDO monomer and copolymerizing it with an alkylated bithiophene ( P42 ) and TVT comonomers, Zhang et al were able to continue with and further expanded this concept (note: P42 – P44 are not shown in Figure due to their close similarities to the other BDO polymers that we have shown in Figure ), reporting electron mobilities of up to 1.86 cm 2 V −1 s −1 * . A similar fluorination strategy to Lei et al was reported by Zheng et al Here they used a tetra‐fluorinated BDO monomer ( P43 ), suggesting that the fluorination might have a double function as a conformational lock.…”
Section: N‐type Organic Semiconductorssupporting
confidence: 62%
“…And a diblock copolymer mPEG-b-PHEP reported previously (Sun et al, 2014). bis(6-bromo-1-(4-decyltetradecyl)-2-oxo-7-azaindolin-3-ylidene)benzo[1,2-b:4,5-b′]-difuran-2,6(3H,7H)-dione (2Br-BABDF), (3,3′-didodecyl-[2,2′-bithiophene]-5,5′-diyl)bis(trimethylstannane) (2tin-BT), ((4,8-bis(5-(2-ethylhexyl)thiophen-2-yl)-6-(trimethylstannyl)benzo[1,2-b:4,5-b']dithiophen-2-yl)dimethylstannyl)methylium (2tin-BDTT), and (E)-1,2-bis(3-dodecyl-5-(trimethylstannyl)thiophen-2-yl)ethene (2tin-TVT) were synthesized according to the methods that reported in documents (Li et al, 2016b; Zhang et al, 2017a). Tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ), tri(o-tolyl)phosphine (P(o-tol) 3 ), and other chemicals were purchased from Sigma-Aldrich Chemical Company, Alfa Aeasar Chemical Company, and Sinopharm Chemical Reagent Co. Ltd., China.…”
Section: Methodsmentioning
confidence: 99%
“…Herein, we currently introduce another isoindigo derivative (BABDF) by replacing the outer benzene rings of BIBDF with aza rings (Figure 1), an obvious next step, synthesize three BABDF-based conjugated polymers (PBABDF-BDTT, PBABDF-BT, and PBABDF-TVT) and study their photothermal properties. On the one hand, the introduction of electronegative N atom could further enhance the electron-withdrawing power of acceptor which result in strong push-pull interaction and significant red-shifts of absorption (Zhang et al, 2017a). On the other hand, the N-substitution on backbone can produce non-covalent interaction (S…N and CH….N) and endows the polymer with improved planar structure, which can also lead the redshift of absorption (Jackson et al, 2013; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…16 This high electron affinity unit was then used to construct other ambipolar and n-type polymers with a maximum electron mobility exceeding 7 cm 2 V À1 s À1 . [17][18][19] We introduced methyl and methoxy groups to modify the structures (hereafter referred to as DMTT for dimethylthienothiophene and MOTT for dimethoxythienothiophene). Methyl substituents can tune the electronic and morphological effects in optoelectronics, [20][21][22] whereas methoxy substituents are used to typically form noncovalent SÁ Á ÁO interactions for highperformance p-type semiconductors.…”
Section: Introductionmentioning
confidence: 99%